Willingness to pay for cooking with electricity among rural households: The case of Southern Ethiopia - Kassahun Trueha Dumga; Kishor Goswami (Heliyon, 2025)
One way to fulfill the worldwide goal of clean energy outlined in SDG 7 is by adopting modern and alternative energy sources, specifically through electric cooking. Most rural households in developing countries, however, lack access to a clean and affordable energy source; thus, a significant part of the population relies on solid fuels. This study investigates the factors influencing households' willingness to pay for electricity services for cooking in rural areas of Southern Ethiopia, where access to clean and affordable energy is limited. A multi-stage cluster sampling design was used to select 571 households from six randomly chosen woredas (districts) in the Southern Nations, Nationalities, and Peoples region. The results show that 45.53 percent of the respondents were willing to pay for electricity for cooking, with a mean WTP of 510.12 Birr, representing a 13.36 percent increase over the current average bill rate. Factors such as total family income, distance from the main road, type of cooking stove, and the number of power outages per day significantly influence households’ willingness to pay for electricity for cooking. Among other reforms, the electricity authority should improve the quality of electric service and access in rural areas. Given the relationship between the WTP for cooking with electricity and household income, it would benefit the government to consider providing subsidies for electricity supply to households with lower incomes.